EFFECT OF GOOD CORPORATE GOVERNANCE ON SALES GROWTH AT “KSU BROSEM” BATU CITY - M. Noerhadi Sudjoni; Dwi Susilowati; Arief Joko Saputro (Journal of Agricultural Socio-Economics (JASE), 2023)
A company needs better corporate governance to survive for long-term growth and survival. Therefore, implementing Good Corporate Governance can support the company's development, especially in KSU BROSEM. The research was conducted at KSU BROSEM Batu City with a purposive sampling method. This type of data uses primary data from interviews from various sources, including managers, heads of finance, and heads of divisions. Data analysis was carried out through three stages: data reduction, data presentation, and conclusions, which were then assessed using a likert scale score. The results obtained from the implementation of GCG at KSU BROSEM Batu City are included in the excellent category, where the average value obtained is 3.66. The application starts from transparency (transparency), accountability (accountability), responsibility (responsibility), independence (independence), and fairness (fairness or equality). Recommendations that can be given are to improve the performance of KSU BROSEM by paying more attention to aspects that can affect the development of KSU BROSEM in the future.